DNMT3A mutation leads to leukemic extramedullary infiltration mediated by TWIST1. Issue 1 (December 2016) - Xu, Jie; Zhang, Wu; Yan, Xiao-Jing; Lin, Xue-Qiu; Li, Wei; Mi, Jian-Qing; Li, Jun-Min; Zhu, Jiang; Chen, Zhu; Chen, Sai-Juan
Abstract Background DNMT3A mutations are frequently discovered in acute myeloid leukemia (AML), associated with poor outcome. Recently, a relapse case report of AML extramedullary disease has showed that AML cells harboringDNMT3A variation were detected in the cerebral spinal fluid. However, whether a causal relationship exists betweenDNMT3A mutation (D3Amut) and extramedullary infiltration (EMI) is unclear. Methods We took advantage ofDNMT3A (R882C) mutation-carrying AML cell strain, that is, OCI-AML3, assessing its migration ability in vitro and in vivo. By RNA interfering technology and a xenograft mouse model, we evaluated the effect ofDNMT3A mutation on cell mobility and explored the possible mechanism. Results OCI-AML3 displayed extraordinary migration ability in vitro and infiltrated into meninges of NOD/SCID mice after intravenous transfusion. We found that this leukemic migration or infiltration capacity was significantly compromised by the knockdown of DNMT3A mutant. Notably, TWIST1, a critical inducer of epithelial–mesenchymal transition, which underlies the metastasis of carcinomas, was highly expressed in association with R882 mutations. Abrogation of TWIST1 inDNMT3A mutated cells considerably weakened their mobility or infiltration. Conclusions Our results demonstrate that D3Amut in OCI-AML3 strain enhances leukemic aggressiveness by promoting EMI process, which is partially through upregulating TWIST1.